Deseo, Placer y Goce en las Trabajadoras WebCam (2021)
This work aims to analyze how Webcam Models mean desire, pleasure and jouissance at the time of developing their work activity, from a psychoanalytic perspective, in which a qualitative study was developed with an exploratory-descriptive scope under a narrative design focused on a historical-hermeneutic research study where individual interviews were conducted with 4 Webcam models between 20 and 30 years of age residing in Bogota selected under the snowball effect; where the data collection will be done through the respective transcripts of the interviews corresponding to each participant through a content analysis, this is how the meaning given by the Webcam models to these psychoanalytic concepts from the economic, social, personal and family factors can be evidenced.